Motor transport network in the Western region of Ukraine as a factor of tourism industry development - Grytsevych, Volodymyr Stefanovych; Podvirna, Khrystyna Yevgenivna; Senkiv, Mariana Igorivna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Formulation of the problem. Infrastructure can be a factor of certain industries’ development in the service sector. Conversely, the development of the service sector may stimulate infrastructure development.Analysis of recent research and publications. Most of the research is devoted to issues of infrastructure and services separately, but not to the mutual influence of infrastructure and services.Selection of previously unsettled parts of the general problem. For studying the peculiarities of the mutual influence of the motor transport network and specific types of tourism in the Western region of Ukraine the motor transport infrastructure was considered as part of general infrastructure and tourism industry as part of service sector.Formulating the purpose of the paper. The purpose of the paper is the human and geographical analysis of the motor transport network of the Western region of Ukraine and spreading of the most developed types of tourism in the region in order to identify the features of their geospatial interdependence.Presentation of the main research material. The network of public automobile roads in the Western region of Ukraine is rather dense, which corresponds to the level of development of the tourism industry in the oblasts. There is a territorial gravity of the subjects of the hotel business and tourist flows to the places of a developed network of automobile roads.In order to analyze the motor transport and tourism spheres for correspondences between them, two classification criteria of types of tourism are selected: according to the way of travel and the purpose of travel. The types of tourism identified for each criterion can be linearly ordered in accordance with the predominant category of automobile roads.Conclusions. Automobile type of tourism uses the ways of travel on all available automobile roads. Cycling type is localized on all types of automobile roads, except international motorways. Pedestrian tourism tends to places where there are no roads of any class at all.Business tourism tends to the administrative and business centers that are on the priority automobile roads. Cognitive tourism tends to the natural, historical and cultural objects, while health tourism tends to the specialized health centers, mainly resorts. Pilgrim and nostalgic tourism occupy mostly lower levels of the hierarchy of automobile roads, although some nostalgic travels can be found in large cities. Fishing and, especially, hunting tourism tends to areas with no automobile roads.